Indirect validation of a retrospective method of exposure assessment used in a nested case-control study of lung cancer and silica exposure. Issue 2 (February 1994) - Dosemeci, M; McLaughlin, J K; Chen, J Q; Hearl, F; McCawley, M; Wu, Z; Chen, R G; Peng, K L; Chen, A L; Rexing, S H
Abstract : Validations of retrospective methods of assessment used in occupational epidemiological studies have rarely been published. This study is an indirect validation of a quantitative retrospective assessment of exposure to silica used in a nested case-control study of lung cancer among workers at 29 metal mines and pottery factories in China. Indices of cumulative total dust and cumulative respirable dust were calculated by merging work histories with the historical exposure profile for each subject. To validate indirectly the methods of exposure assessment used in the study of lung cancer, trends for exposure response relation between the two indices of exposure to silica and risk of silicosis were evaluated with 376 patients with silicosis from the study population as the cases, and 1262 controls without silicosis for comparison. Age adjusted odds ratios (ORs) as a measure of risk of silicosis showed striking trends with both indices of exposure to silica. For cumulative respirable dust, the OR (95% confidence interval) rose from 7.6 (5.1-11.4) for low exposure to 20.0 (13.2-30.6) for medium exposure, and to 51.7 (31.0-86.8) for high exposure. The strength of the association between exposure to silica and risk of silicosis suggests that the retrospective assessment of exposure used in the case-control study of lung cancer would accurately reflect an exposure response relation between silica and lung cancer, if it existed.